Laboratory exercises in environmental geology - Blatt, Harvey (McGraw-Hill, 1998)
This laboratory manual has been fine-tuned to fulfill the needs of an introductory course for majors and non-majors. Reduced math and chemistry coverage and condensed lab exercises make the manual more manageable for one-semester course, while offering a range of problems to match each student's abilities. Lab exercises focus on a broad range of environmental issues and include full-color photography to make identification problems easier. Author also covers the social issues relevant to environmental concerns and the effects of human intervention in geological processes.